Methodological Quality of Systematic Reviews in Brazilian Psychology Journals Quality of systematic reviews in Psychology - Zoltowski, Ana Paula Couto (2014)
The aim of this study is to measure the methodological quality of systematic reviews (SR) published in Brazilian psychology journals. It was conducted a SR in SciELO and PePSIC databases, using “review” and “systematic” as keywords. 33 articles were identified and analyzed using the Assessment of Multiple Systematic Reviews (AMSTAR). The mean value of quality was 5.39 (SD = 1.91) on a scale ranging from 0 to 11. Using criteria of Qualis CAPES, significant differences were found in the quality of RS published in SciELO compared to those published in PePSIC, but not according to the journal extract. No increase in quality was observed from 2001 to 2012. The adoption of guidelines for publication of SR is suggested, in order to improve their quality in Brazil.